The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-63032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Tumor Mutation Burden and Immune Infiltrates in Hepatocellular Carcinoma Based on Multi-Omics Analysis

Abstract: Background: We aimed to explore the tumor mutational burden (TMB) and immune infiltration in HCC and investigate new biomarkers for immunotherapy.Methods: Transcriptome and gene mutation data were downloaded from the GDC portal, including 374 HCC samples and 50 matched samples. Furthermore, we divided the samples into high and low TMB groups, and analyzed the differential genes between them with GO, KEGG, and GSEA. Cibersort was used to assess the immune cell infiltration in the samples. Finally, univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…At the same time, we also found that the most frequent type of non-nonsense mutation, whether in the low-or high-risk group, was a missense mutation. The top 3 genes with the highest frequency were TP53, TTN, and CTNNB1, respectively, which was consistent with previous studies (39,40). However, we found that the genes with the highest mutation frequency among high-and lowrisk groups differed, with CTNNB1 highest in the low-risk group and TP53 highest in the high-risk group.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, we also found that the most frequent type of non-nonsense mutation, whether in the low-or high-risk group, was a missense mutation. The top 3 genes with the highest frequency were TP53, TTN, and CTNNB1, respectively, which was consistent with previous studies (39,40). However, we found that the genes with the highest mutation frequency among high-and lowrisk groups differed, with CTNNB1 highest in the low-risk group and TP53 highest in the high-risk group.…”
Section: Discussionsupporting
confidence: 91%
“…Tissue-agnostic biomarkers such as tumour mutation burden (TMB) and MSI have been examined for cancer immunotherapy [57][58][59]. TMB has been utilised as a predictive biomarker in cancer immunotherapy in several studies [11,[60][61][62]. Our previous study demonstrated significant association of TMB with poor clinical outcomes in HCC patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its high speci city and can be recognized by immune cells, it is the target of personalized therapeutic cancer vaccines [36]. Previous studies have con rmed thatMUC16 is associated with TMB in hepatocellular carcinoma and gastric cancer [37,38]. MUC family proteins are highly related to MSI in colon cancer [39].…”
Section: Discussionmentioning
confidence: 99%